The 'Good Friday Agreement' and cancer research on the island of Ireland: Evidence for the impact of a tripartite cancer research partnership. (April 2020) - Lewison, Grant; Gavin, Anna; McCallion, Karen; McDermott, Ray; Sullivan, Richard; Lawler, Mark
Abstract: Aim: In 1999, a cooperative tripartite cancer research and training agreement was signed between Ireland (IE), Northern Ireland (NI) and the United States (US) National Cancer Institute, giving rise to the All-Ireland Cancer Consortium (AICC). We wished to consider if AICC increased the amount/impact of cancer research on the island of Ireland and what effect this enhanced research activity had on cancer services and cancer outcomes. Methods: As comparator, we chose the city regions of Copenhagen and Lund & Malmö, whose physical connection was greatly improved following construction of bridges between Denmark and Sweden around the time AICC was established. We analysed cancer research outputs from all four geographical regions in the Web of Science (1988–2017), with a particular focus on citations and journal impact factors. We evaluated disability-adjusted life years (DALYs) as an indicator of change in health status. Results: Research outputs increased in all four regions, but more in IE/NI than in the Scandinavian cities, while collaboration between IE and NI and both the US and the Rest of Europe increased even more substantially. Citation scores also showed a greater improvement for IE and NI. Journal citation impact factors indicated that IE/NI papers were increasingly being published in more highly cited journals. Research-enabled cancer service provision improved on the island of Ireland, with concomitant increases in cancer survival. Conclusion: The AICC collaborative agreement delivered significant additionality on the island of Ireland, promoting transnational cooperation, enhancing cancer research activity, and underpinning improved cancer services and better cancer outcomes. Highlights: The All-Ireland Cancer Consortium led to: ○ Increased research outputs on the island of Ireland. ○ Enhanced collaboration. ○ Improved citations and enhanced impact. ○ Improved cancer services and increased cancer survival.